A high heat dissipation lead frame for semiconductor packaging and a manufacturing method thereof

By using a composite layer structure of copper-based materials and carbon nanotubes in the lead frame, combined with anodizing and laser cladding processes, the lead frame's insufficient efficiency in chip heat dissipation is solved, and higher thermal conductivity and heat resistance are achieved.

CN119208153BActive Publication Date: 2025-03-07TAIZHOU DONGTIAN ELECTRONICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411324454.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-03-07
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing lead frames have insufficient efficiency in chip heat dissipation, which leads to the chip being prone to overheating.

Method used

Using copper-based materials as the basis, a composite layer is formed by adding magnesium, chromium and rare earth elements, combined with the addition of carbon nanotubes, to improve thermal conductivity, and the bonding strength and corrosion resistance of the oxide film and composite layer are enhanced through anodizing and laser cladding processes.

Benefits of technology

It significantly improves the thermal conductivity and mechanical strength of the lead frame, enhances its heat resistance and corrosion resistance, thereby effectively reducing the temperature of the chip.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high heat dissipation lead frame for semiconductor packaging and a manufacturing method thereof, which relates to the technical field of lead frames, and includes the following processes: placing a copper base in an electrolyte for anodization to form an oxide film; taking aluminum, nickel, yttrium, and composite carbon nanotubes as cladding materials, laying them on the surface of the oxide layer, and performing laser cladding to form a composite layer to obtain a high heat dissipation lead frame, and improving the thermal conductivity of the copper base by configuring the copper base components and adding carbon nanotubes, and exerting the strengthening effect of the second phase to alleviate the dissolution and grain boundary softening of the precipitated phase at high temperature, and improving the mechanical properties of the copper base while improving its heat resistance. A precursor is prepared with carbon nanotubes, sodium tungstate, and hydrochloric acid, and carbonized to form composite carbon nanotubes, which are introduced into the electrolyte used for anodization to improve the corrosion resistance of the prepared lead frame; and the electrical and thermal conductivity of the prepared oxide film are improved, and the heat dissipation effect and mechanical strength of the lead frame are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lead frames, in particular to a high heat dissipation lead frame for semiconductor packaging and a manufacturing method thereof. Background Art

[0002] With the rapid development of informatization, the electronics industry, as the engine of the information society, is changing the production and lifestyle of human beings. Electronic components are the cornerstone supporting the rapid development of the electronics industry and the key to ensuring the stability of the industrial chain. As an important mechanical support carrier for chips in electronic components, the lead frame plays the role of fixing and supporting chips, heat dissipation, signal transmission, power distribution, etc., and is an extremely critical electronic component. The increase in chip integration increases the heat generated by the chip during operation, which is prone to overheating inside the integrated circuit, and the heat needs to be dissipated to the outside in time through the lead frame. Therefore, we propose a high heat dissipation lead frame for semiconductor packaging and a method for making it. Summary of the invention

[0003] The object of the present invention is to provide a high heat dissipation lead frame for semiconductor packaging and a manufacturing method thereof, so as to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a high heat dissipation lead frame for semiconductor packaging, comprising a copper base, an oxide film and a composite layer.

[0005] Furthermore, the copper base is one of copper-iron-phosphorus, copper-nickel-silicon, copper-chromium-zirconium, copper-silver, and copper-tin alloy systems.

[0006] Furthermore, the copper matrix includes the following mass components: 2.1-2.6% Fe (iron), 0.02-0.10% P (phosphorus), 0.05-0.20% Zn (zinc), 0.02-0.08% Mg (magnesium), 0.02-0.08% Cr (chromium), 0.06-0.10% Y (yttrium), 0.3-1.0% carbon nanotubes, and the balance is Cu (copper).

[0007] Furthermore, the copper base has a thickness of 0.10 to 0.25 mm.

[0008] Furthermore, the copper base is heat treated, and the specific process is as follows: keeping the temperature at 520-550°C for 100-150 minutes; keeping the temperature at 450-480°C for 100-150 minutes.

[0009] In the above technical scheme, the copper-based material is selected from the copper-iron-phosphorus system, which has good strength, electrical conductivity, softening resistance, processing, electroplating, and brazing performance, and is suitable for the preparation of electronic devices. As a lead frame, it has good electrical conductivity, thermal conductivity, mechanical strength, and processability. On the basis of the copper-iron-phosphorus alloy, magnesium, chromium, and rare earth elements are added to effectively refine the grains of the alloy structure, improve the strength and toughness of the copper base, and improve its electrical conductivity to a certain extent. Among them, magnesium and rare earth elements can deoxidize and purify the melt during alloy smelting, which helps to remove gases and impurities therein; rare earth elements can also combine with hydrogen to alleviate the hydrogen embrittlement phenomenon of the copper base; this has a good promoting effect on increasing the effective content of alloy elements, and the number of precipitated phases is increased, which can hinder the recrystallization and improve the heat resistance of the copper base. The chromium element has a high melting point, which can effectively increase the recrystallization temperature of the copper base; the second phase and solid solution atoms are formed, which improves the mechanical strength and heat resistance of the copper base.

[0010] Carbon nanotubes can transfer heat through lattice vibration phonons, which improves the thermal conductivity of the copper base. They also have a low expansion coefficient, which can alleviate the reduction in thermal conductivity caused by thermal expansion, thereby improving the thermal conductivity of the copper base and reducing the interface thermal resistance between the copper base and the chip. At the same time, carbon nanotubes can play a second phase strengthening role, easing the dissolution of the precipitated phase and grain boundary softening at high temperatures, and can improve the mechanical properties of the copper base while improving its heat resistance.

[0011] A method for manufacturing a high heat dissipation lead frame for semiconductor packaging, comprising the following processes:

[0012] The copper base is placed in an electrolyte for anodization to form an oxide film;

[0013] Aluminum, nickel, yttrium and composite carbon nanotubes are taken as cladding materials, laid on the surface of the oxide layer, and laser cladding is performed to form a composite layer to obtain a high heat dissipation lead frame.

[0014] Furthermore, the specific process conditions of anodization are: using a copper base as an anode and titanium as a cathode, passing a constant current into the electrolyte to perform anodization to form an oxide film;

[0015] Current density 0.5~1.0A / dm 2 , temperature 65 ~ 70 ℃, duration 20 ~ 30 minutes.

[0016] Furthermore, the electrolyte used for anodization includes the following mass components: 40-60 g / L sodium hydroxide, 100-150 g / L sodium chloride, 0.5-2.0 g / L polyethylene glycol, 0.4-0.6 g / L carbon nanotubes, and the solvent is deionized water.

[0017] In the above technical solution, anodization forms a copper oxide nanoarray on the copper substrate surface, which is referred to as an oxide film. This can effectively increase the specific surface area of ​​the copper substrate, improve the bonding strength between the copper substrate and the composite layer, and contribute to improving the tensile strength and corrosion resistance of the produced lead frame.

[0018] Furthermore, the carbon nanotubes are subjected to composite modification, and the specific process is as follows:

[0019] Sodium tungstate, water and carbon nanotubes are mixed, heated to 75-82°C, concentrated hydrochloric acid is slowly added within 10-15 minutes, heated to 98-102°C, refluxed and kept warm for 210-270 minutes; centrifuged and dried to obtain a precursor; carbonized at high temperature to obtain composite carbon nanotubes.

[0020] Further, the mass ratio of sodium tungstate and carbon nanotubes is (39-41):0.1;

[0021] The carbon nanotubes are added in the form of ethylene glycol dispersion, and the concentration of the carbon nanotube ethylene glycol dispersion is 0.1 g / L;

[0022] The ratio of sodium tungstate to water is (3.9-4.1) g:100 mL;

[0023] The mass concentration of concentrated hydrochloric acid is 37%; the ratio of carbon nanotubes to concentrated hydrochloric acid is (0.10-0.13) g:100 mL.

[0024] Furthermore, the carbonization process conditions are as follows: nitrogen is introduced and air replacement is completed within 30 minutes; under the protection of nitrogen atmosphere, the temperature is increased to 580-620°C at a heating rate of 300-400°C / h;

[0025] Then, a carbon source is introduced and the temperature is raised to 880-920° C., and the reaction is kept at this temperature for 60-90 minutes; nitrogen is continuously introduced, the temperature is lowered to below 300° C., and the mixture is taken out and air-cooled to room temperature.

[0026] Further, the carbon source flow rate is 10-15 mL / h;

[0027] The carbon source is a mixed gas of methanol and ethanol, and the concentration of ethanol is 15-25wt%.

[0028] In the above technical solution, carbon nanotubes are mixed with sodium tungstate and hydrochloric acid and refluxed. Under the strong oxidizing effect of concentrated hydrochloric acid, carbon nanotubes are oxidized to form a large number of oxygen-containing functional groups and increase the specific surface area, so that a large amount of tungstic acid is deposited on the surface of carbon nanotubes to form a precursor (tungstic acid / carbon nanotubes). Then, under the protection of nitrogen atmosphere, methanol and ethanol are introduced as reducing agents and carbon sources to carbonize tungstic acid to form tungsten carbide; excess carbon is deposited on the surface of tungsten carbide to generate graphene, and the structural defects of carbon nanotubes can be repaired to form composite carbon nanotubes.

[0029] In the above technical solution, the composite carbon nanotubes are added to the electrolyte used for anodization, thereby obtaining an oxide film containing the composite carbon nanotubes on the surface of the copper base. The composite carbon nanotubes fill the pores and defects of the oxide film, play a pore sealing effect, can hinder the penetration of the corrosive medium into the copper base, and improve the corrosion resistance of the prepared lead frame. If there are too many composite carbon nanotubes, in the later stage of anodization, the dissolution rate of the film layer increases, the thickness of the film layer decreases, the pores of the oxide film become larger, and the density of the film layer decreases, which will cause the deterioration of its corrosion resistance.

[0030] Tungsten carbide, carbon nanotubes, and graphene are all good conductors of electricity and heat. Adding them to the electrolyte can improve the electrical and thermal conductivity of the oxide film, and improve the heat dissipation effect and mechanical strength of the lead frame. However, pure tungsten carbide is relatively brittle. Through the above process, it is compounded with carbon nanotubes and graphene, recorded as composite carbon nanotubes, so that it has three-dimensional dimensions and maintains good performance in all directions. While further improving its electrical and thermal conductivity, it can effectively enhance its toughness, ensure the low thermal expansion coefficient of the copper-based surface, and the stability of the bonding between the lead frame and the chip, avoiding holes in the bonding area, and negatively affecting the interface thermal resistance.

[0031] Furthermore, the copper base includes the following mass components: 2.1-2.6% Fe (iron), 0.02-0.10% P (phosphorus), 0.05-0.20% Zn (zinc), 0.02-0.08% Mg (magnesium), 0.02-0.08% Cr (chromium), 0.06-0.10% Y (yttrium), 0.3-1.0% composite carbon nanotubes, and the balance is Cu (copper).

[0032] In the above technical scheme, the prepared composite carbon nanotubes are added to the copper-based matrix. The good wetting performance of copper on the tungsten carbide loaded thereon and the diffusion of tungsten into copper help to improve the interface bonding between the copper-based and composite carbon nanotubes, making it as the second phase and improving the toughness of the copper-based. The carbon nanotubes inside and the graphene on the surface can reduce its specific gravity, prevent the sinking and segregation of the composite carbon nanotubes in copper, and help to homogenize the components; and can alleviate the interface problems caused by cooling, eliminate the defects of the copper-based containing tungsten carbide, and improve its mechanical properties, electrical conductivity and thermal conductivity. In addition, graphene also has phonon heat transfer ability, and the high thermal conductivity and low specific heat capacity of the composite carbon nanotubes can accelerate the transfer speed of heat, which is conducive to the improvement of the thermal conductivity and heat dissipation performance of the copper-based to a certain extent.

[0033] Furthermore, the process conditions of laser cladding are: argon gas flow rate of 15-25 L / min, spot diameter of 3-5 mm, scanning speed of 9-15 mm / s, and laser power of 1.5-2.0 kW.

[0034] Furthermore, the cladding material includes 10 to 20 parts of carbon nanotubes, 2 to 3 parts of aluminum, 1 to 3 parts of Ni276, and 1 to 2 parts of yttrium;

[0035] Using 8-10% sodium silicate solution as a binder, the cladding material is evenly coated on the surface of the oxide layer with a coating thickness of 50-100 μm;

[0036] The mass ratio of the binder to the cladding material is 18 to 35%.

[0037] In the above technical solution, compared with copper-based materials, carbon nanotubes (composite carbon nanotubes) have the characteristics of low specific heat and high thermal conductivity, which makes the lead frame have good thermal conductivity. Aluminum and nickel both have high specific heat capacity, which makes the lead frame have good ability to store and transfer heat, and cooperate with carbon nanotubes (composite carbon nanotubes) to improve the heat dissipation efficiency of the lead frame.

[0038] The tungsten carbide in the composite carbon nanotubes has a high absorbance and can absorb more laser energy, promote its melting, diffuse elements with the surrounding, form composition fluctuations in the composite layer, and can serve as a nucleation core to promote heterogeneous nucleation, achieve grain refinement, and improve the mechanical strength of the composite layer.

[0039] Anodizing of the copper base alleviates the dilution effect of laser cladding on the cladding material to a certain extent; the rare earth element yttrium increases the fluidity of the molten pool; at the same time, higher laser scanning power is conducive to element diffusion; higher scanning speed accelerates the cooling of the molten pool and prevents the diffusion of elements at the front of the crystallization interface, which makes the composite layer formed by laser cladding have better quality.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. The high heat dissipation lead frame for semiconductor packaging described in the present invention improves the thermal conductivity of the copper base by configuring the copper base components and adding carbon nanotubes, and exerts the strengthening effect of the second phase to alleviate the dissolution of the precipitated phase and the softening of the grain boundaries at high temperatures, thereby improving the mechanical properties of the copper base and improving its heat resistance.

[0042] 2. The high heat dissipation lead frame for semiconductor packaging described in the present invention is prepared by preparing a precursor through carbon nanotubes, sodium tungstate, and hydrochloric acid, carbonizing to form composite carbon nanotubes, and introducing them into the electrolyte used for anodization to improve the corrosion resistance of the prepared lead frame; and improve the electrical and thermal conductivity of the prepared oxide film, thereby improving the heat dissipation effect and mechanical strength of the lead frame. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In the following specific implementations,

[0045] The raw material was melted at 1420℃, poured into a 250mm×75mm×20mm mold, and water quenched at 830℃×1h for solid solution; 940℃×75% hot rolling, 70% cold rolling, at 535℃, heat preservation for 120min; 75% cold rolling, at 465℃, heat preservation for 120min; 60% cold rolling, at 300℃, heat preservation for 120min, to obtain a copper base;

[0046] In Examples 1-3, the copper matrix includes the following mass components: 2.35% Fe, 0.04% P, 0.13% Zn, 0.05% Mg, 0.05% Cr, 0.06% Y, 0.7% composite carbon nanotubes, and the balance is Cu;

[0047] Carbon nanotubes: outer diameter of tube wall 20-30nm, length 20-30μm, purity>95%, sourced from Beijing NanoCenter Technology Co., Ltd.

[0048] Polyethylene glycol: 20000, from Merck Chemicals;

[0049] Aluminum: purity> 99.9%, particle size 20-30 mesh, sourced from Changsha Xinkang New Materials Co., Ltd.;

[0050] Ni276: purity ≥999%, 300 mesh, from Qinghe County Benyu Metal Materials Co., Ltd. Yttrium: purity >99.9%, Changsha Xinkang New Materials Co., Ltd.;

[0051] The carbon nanotubes are added in the form of ethylene glycol dispersion, the concentration of which is 0.1 g / L; the mass concentration of concentrated hydrochloric acid is 37%.

[0052] Embodiment 1: A method for manufacturing a high heat dissipation lead frame for semiconductor packaging, comprising the following processes:

[0053] Step 1, preparation of composite carbon nanotubes: sodium tungstate, water and carbon nanotubes are mixed, heated to 75°C, concentrated hydrochloric acid is slowly added within 10 minutes, heated to 98°C, refluxed and kept warm for 210 minutes; centrifuged and dried to obtain a precursor; the mass ratio of sodium tungstate to carbon nanotubes is 39:0.1; the ratio of sodium tungstate to water is 3.9g:100mL; the ratio of carbon nanotubes to concentrated hydrochloric acid is 0.10g:100mL;

[0054] Carbonization: nitrogen was introduced and air replacement was completed within 30 minutes; under the protection of nitrogen atmosphere, the temperature was raised to 580°C at a heating rate of 300°C / h; then a carbon source was introduced and the temperature was raised to 880°C, and the reaction was kept warm for 60 minutes; nitrogen was continuously introduced, the temperature was lowered to below 300°C, and the mixture was taken out and air-cooled to room temperature to obtain composite carbon nanotubes; the carbon source flow rate was 10 mL / h; the carbon source was a mixed gas of methanol and ethanol, and the ethanol concentration was 15wt%;

[0055] Step 2: Anodization: With copper as anode and titanium as cathode, a constant current is passed through the electrolyte to perform anodization to form an oxide film; the current density is 0.5A / dm 2 , temperature 65°C, duration 20min; the electrolyte includes the following mass components: 40g / L sodium hydroxide, 100g / L sodium chloride, 0.5g / L polyethylene glycol, 0.4g / L composite carbon nanotubes, and the solvent is deionized water;

[0056] Step 3, laser cladding: take 10 parts of composite carbon nanotubes, 3 parts of aluminum, 3 parts of Ni276, and 2 parts of yttrium as cladding materials, use 8% sodium silicate solution as a binder, and the mass ratio of the binder to the cladding material is 18%; the cladding material is evenly coated on the surface of the oxide layer with a coating thickness of 50 μm, and laser cladding is performed with an argon flow rate of 15 L / min, a spot diameter of 3 mm, a scanning speed of 9 mm / s, and a laser power of 1.5 kW; a composite layer is formed to obtain a high heat dissipation lead frame.

[0057] Embodiment 2: A method for manufacturing a high heat dissipation lead frame for semiconductor packaging, comprising the following processes:

[0058] Step 1, preparation of composite carbon nanotubes: sodium tungstate, water and carbon nanotubes are mixed, heated to 80°C, concentrated hydrochloric acid is slowly added within 12 minutes, heated to 100°C, refluxed and kept warm for 240 minutes; centrifuged and dried to obtain a precursor; the mass ratio of sodium tungstate to carbon nanotubes is 40:0.1; the ratio of sodium tungstate to water is 4.0g:100mL; the ratio of carbon nanotubes to concentrated hydrochloric acid is 0.12g:100mL;

[0059] Carbonization: nitrogen was introduced and air replacement was completed within 30 minutes; under the protection of nitrogen atmosphere, the temperature was raised to 600°C at a heating rate of 350°C / h; then a carbon source was introduced and the temperature was raised to 900°C, and the reaction was kept warm for 75 minutes; nitrogen was continuously introduced, the temperature was lowered to below 300°C, and the mixture was taken out and air-cooled to room temperature to obtain composite carbon nanotubes; the carbon source flow rate was 12 mL / h; the carbon source was a mixed gas of methanol and ethanol, and the ethanol concentration was 20 wt%;

[0060] Step 2: Anodization: With copper as anode and titanium as cathode, a constant current is passed through the electrolyte to perform anodization to form an oxide film; the current density is 0.7A / dm 2 , temperature 68°C, duration 25min; the electrolyte includes the following mass components: 50g / L sodium hydroxide, 125g / L sodium chloride, 1.2g / L polyethylene glycol, 0.5g / L composite carbon nanotubes, and the solvent is deionized water;

[0061] Step 3, laser cladding: take 15 parts of composite carbon nanotubes, 2.5 parts of aluminum, 2 parts of Ni276, and 1.5 parts of yttrium as cladding materials, use 9% sodium silicate solution as binder, and the mass ratio of binder to cladding material is 25%; evenly apply the cladding material on the surface of the oxide layer with a coating thickness of 70 μm, and perform laser cladding with an argon flow rate of 20 L / min, a spot diameter of 4 mm, a scanning speed of 12 mm / s, and a laser power of 1.7 kW; form a composite layer to obtain a high heat dissipation lead frame.

[0062] Embodiment 3: A method for manufacturing a high heat dissipation lead frame for semiconductor packaging, comprising the following processes:

[0063] Step 1, preparation of composite carbon nanotubes: sodium tungstate, water and carbon nanotubes are mixed, heated to 82°C, concentrated hydrochloric acid is slowly added within 15 minutes, heated to 102°C, refluxed and kept warm for 270 minutes; centrifuged and dried to obtain a precursor; the mass ratio of sodium tungstate to carbon nanotubes is 41:0.1; the ratio of sodium tungstate to water is 4.1g:100mL; the ratio of carbon nanotubes to concentrated hydrochloric acid is 0.13g:100mL;

[0064] Carbonization: nitrogen was introduced and air replacement was completed within 30 minutes; under the protection of nitrogen atmosphere, the temperature was raised to 620°C at a heating rate of 400°C / h; then a carbon source was introduced and the temperature was raised to 920°C, and the reaction was kept warm for 90 minutes; nitrogen was continuously introduced, the temperature was lowered to below 300°C, and the mixture was taken out and air-cooled to room temperature to obtain composite carbon nanotubes; the carbon source flow rate was 15 mL / h; the carbon source was a mixed gas of methanol and ethanol, and the ethanol concentration was 25wt%;

[0065] Step 2: Anodization: With copper as anode and titanium as cathode, a constant current is passed through the electrolyte to perform anodization to form an oxide film; the current density is 1.0 A / dm 2 , temperature 70°C, duration 30min; the electrolyte includes the following mass components: 60g / L sodium hydroxide, 150g / L sodium chloride, 2.0g / L polyethylene glycol, 0.6g / L composite carbon nanotubes, and the solvent is deionized water;

[0066] Step 3, laser cladding: take 20 parts of composite carbon nanotubes, 2 parts of aluminum, 1 part of Ni276, and 1 part of yttrium composite as cladding materials, use 10% sodium silicate solution as binder, and the mass ratio of binder to cladding material is 35%; evenly apply the cladding material on the surface of the oxide layer with a coating thickness of 100 μm, and perform laser cladding with an argon flow rate of 25 L / min, a spot diameter of 5 mm, a scanning speed of 15 mm / s, and a laser power of 2.0 kW; form a composite layer to obtain a high heat dissipation lead frame.

[0067] Comparative Example 1: A method for manufacturing a high heat dissipation lead frame for semiconductor packaging, comprising the following processes:

[0068] Step 1: Anodization is the same as in Example 1 to form an oxide film;

[0069] Step 2, laser cladding: take 10 parts of carbon nanotubes, 3 parts of aluminum, 3 parts of Ni276, and 2 parts of yttrium as a composite cladding material, use 8% sodium silicate solution as a binder, and the mass ratio of the binder to the cladding material is 18%; the cladding material is evenly coated on the surface of the oxide layer with a coating thickness of 50 μm, and laser cladding is performed with an argon flow rate of 15 L / min, a spot diameter of 3 mm, a scanning speed of 9 mm / s, and a laser power of 1.5 kW; a composite layer is formed to obtain a high heat dissipation lead frame.

[0070] Comparative Example 2: A method for manufacturing a high heat dissipation lead frame for semiconductor packaging, comprising the following processes:

[0071] Step 1, anodization: using copper as anode and titanium as cathode, a constant current is passed through the electrolyte to perform anodization to form an oxide film; the current density is 0.5A / dm2, the temperature is 65°C, and the duration is 20min; the electrolyte includes the following mass components: 40g / L sodium hydroxide, 100g / L sodium chloride, 0.5g / L polyethylene glycol, 0.4g / L carbon nanotubes, and the solvent is deionized water;

[0072] The copper matrix includes the following mass components: 2.30% Fe, 0.04% P, 0.13% Zn, 0.05% Mg, 0.05% Cr, 0.05% Y, 0.65% carbon nanotubes, and the balance is Cu;

[0073] Step 2 is the same as that of comparative example 1, forming a composite layer to obtain a high heat dissipation lead frame.

[0074] Comparative Example 3: A method for manufacturing a high heat dissipation lead frame for semiconductor packaging, comprising the following processes:

[0075] Step 1, anodization: With copper as anode and titanium as cathode, a constant current is passed through the electrolyte to perform anodization to form an oxide film; the current density is 0.5A / dm2, the temperature is 65°C, and the duration is 20min; the electrolyte includes the following mass components: 40g / L sodium hydroxide, 100g / L sodium chloride, 0.5g / L polyethylene glycol, and the solvent is deionized water;

[0076] The copper matrix includes the following mass composition: 2.30% Fe, 0.04% P, 0.13% Zn, 0.05% Y, and the balance is Cu;

[0077] Step 2 is the same as that of comparative example 2, forming a composite layer to obtain a high heat dissipation lead frame.

[0078] Experiment: Take the lead frames obtained in Examples 1-3 and Comparative Examples 1-3, prepare samples, test their performances respectively and record the test results:

[0079] Corrosion resistance test: three-electrode electrochemical corrosion detection was used, with the sample as the test electrode, graphite as the auxiliary electrode, saturated calomel as the reference electrode, the medium as a neutral 3.5wt% sodium chloride aqueous solution, the scanning range was -2 to 2V, and the rate was 120mV / s;

[0080] Mechanical properties test: The tensile strength of the sample was tested using an electronic universal testing machine with a tensile rate of 2 mm / min;

[0081] Heat dissipation performance test: A 20mm×20mm ceramic heating sheet with a heating power of 10W was used as the heat source to detect the heat dissipation efficiency of the sample. The room temperature was 24°C, and a copper-based (including the following mass components: 2.32% Fe, 0.050% P, 0.12% Zn, and the remainder was Cu) group was used as the blank group. The heat source temperature was detected at thermal equilibrium, and the rate of change of the two ((TT 空白 ) / T 空白 ×100%) as the heat dissipation performance index;

[0082] Conductivity test: Use eddy current conductivity meter to detect the conductivity of the sample.

[0083] Tensile strength(MPa) Conductivity (%IACS) Rate of change (%) <![CDATA[Corrosion current density (×10 -6 A / cm 2 )]]> Example 1 553 60.2 -20.6 1.73 Example 2 568 61.6 -21.4 1.12 Example 3 570 62.1 -22.1 1.39 Comparative Example 1 529 59.3 -18.3 3.46 Comparative Example 2 521 58.5 -17.7 4.13 Comparative Example 3 486 57.2 -15.8 7.31

[0084] According to the data in the above table, we can clearly draw the following conclusions:

[0085] The lead frames obtained in Examples 1-3 are compared with the lead frames obtained in Comparative Examples 1-3. The test results show that:

[0086] Compared with the comparative example, the lead frames obtained in Examples 1-3 have more excellent tensile strength, electrical conductivity, change rate, and corrosion current density data, which fully demonstrates that the present invention improves the heat dissipation capacity of the prepared lead frame and enables the lead frame to maintain relatively excellent mechanical strength, electrical conductivity, and corrosion resistance.

[0087] Compared with Example 1, the composite carbon nanotubes are replaced with carbon nanotubes in the laser cladding process of Comparative Example 1; the composite carbon nanotubes are replaced with carbon nanotubes in the anodizing and laser cladding processes of Comparative Example 2; the copper-based components in Comparative Example 3 are different, and carbon nanotubes are not used in the anodizing process. The lead frames obtained in Comparative Examples 1-3 have deteriorated tensile strength, electrical conductivity, rate of change, and corrosion current density data. It can be seen that the present invention can promote the comprehensive improvement of its heat dissipation capacity, mechanical strength, electrical conductivity, and corrosion resistance by setting the lead frame process and the components used.

[0088] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for manufacturing a high heat dissipation lead frame for semiconductor packaging, characterized in that: Including the following processes: The copper base is placed in an electrolyte for anodization to form an oxide film; Aluminum, nickel, yttrium and composite carbon nanotubes are used as cladding materials, laid on the surface of the oxide layer, and laser cladding is performed to form a composite layer to obtain a high heat dissipation lead frame; The composite carbon nanotubes are prepared by carbonizing a precursor using carbon nanotubes, sodium tungstate and concentrated hydrochloric acid as raw materials; The copper matrix comprises the following mass components: 2.1-2.6% Fe, 0.02-0.10% P, 0.05-0.20% Zn, 0.02-0.08% Mg, 0.02-0.08% Cr, 0.06-0.10% Y, 0.3-1.0% composite carbon nanotubes, and the balance is Cu.

2. The method for manufacturing a high heat dissipation lead frame for semiconductor packaging according to claim 1, characterized in that: The carbonization process conditions are as follows: introducing nitrogen and completing air replacement within 30 minutes; under the protection of nitrogen atmosphere, heating to 580-620°C at a heating rate of 300-400°C / h; then introducing a carbon source and heating to 880-920°C, and keeping the temperature for reaction for 60-90 minutes; continuously introducing nitrogen, cooling to below 300°C, and taking out and air cooling to room temperature.

3. The method for manufacturing a high heat dissipation lead frame for semiconductor packaging according to claim 1, characterized in that: The process conditions of the anodizing are: current density 0.5-1.0 A / dm2, temperature 65-70°C, and duration 20-30 min.

4. The method for manufacturing a high heat dissipation lead frame for semiconductor packaging according to claim 1, characterized in that: The electrolyte comprises the following components by mass: 40-60 g / L sodium hydroxide, 100-150 g / L sodium chloride, 0.5-2.0 g / L polyethylene glycol, 0.4-0.6 g / L carbon nanotubes, and the solvent is deionized water.

5. The method for manufacturing a high heat dissipation lead frame for semiconductor packaging according to claim 1, characterized in that: The process conditions of the laser cladding are: argon gas flow rate of 15-25 L / min, spot diameter of 3-5 mm, scanning speed of 9-15 mm / s, and laser power of 1.5-2.0 kW.

6. The method for manufacturing a high heat dissipation lead frame for semiconductor packaging according to claim 1, characterized in that: The cladding material includes 10 to 20 parts of carbon nanotubes, 2 to 3 parts of aluminum, 1 to 3 parts of Ni276, and 1 to 2 parts of yttrium.

7. The method for manufacturing a high heat dissipation lead frame for semiconductor packaging according to claim 1, characterized in that: The mass ratio of sodium tungstate to carbon nanotubes is (39-41):0.1; the ratio of carbon nanotubes to concentrated hydrochloric acid is (0.10-0.13) g:100 mL.

8. A high heat dissipation lead frame for semiconductor packaging is manufactured according to the manufacturing method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of small-size low-cost SMD packaged VCSEL

    CN110661169A

  • High-reliability lead frame and preparation method thereof

    CN116479485A